2008
DOI: 10.1177/021849230801600308
|View full text |Cite
|
Sign up to set email alerts
|

Postinfarction Ventricular Septal Defect: Patch Repair with Infarct Exclusion

Abstract: Postinfarction rupture of the interventricular septum is usually fatal without prompt surgical intervention. Repair of postinfarction ventricular septal rupture by an endocardial patch technique with infarct exclusion is associated with less morbidity and mortality. The results of this repair in 22 consecutive patients were analyzed retrospectively. After myocardial infarction, 16 patients were operated on within 7 days, 3 at 8-21 days, and 3 at 3-6 weeks. 2D-echocardiography, color Doppler studies and coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
1
Order By: Relevance
“…Most studies within this decade across the world have reported 23% to 38% early mortality (30-day or hospital mortality). [6][7][8]15,16 We accept emergency cardiac surgical referrals from the whole territory, and overall 30-day mortality in our current series was 20%. However, no attempt at a direct comparison was made because the differences in outcomes among centers and different time periods probably reflect the differences in referral patterns and recruitment for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies within this decade across the world have reported 23% to 38% early mortality (30-day or hospital mortality). [6][7][8]15,16 We accept emergency cardiac surgical referrals from the whole territory, and overall 30-day mortality in our current series was 20%. However, no attempt at a direct comparison was made because the differences in outcomes among centers and different time periods probably reflect the differences in referral patterns and recruitment for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns were also noticed in other smaller Asian series. [5][6][7][8] In our cohort, postoperative renal failure requiring peritoneal dialysis or hemodialysis was the most common complication and it was predictive of 30-day mortality, and this was also statistically related to preoperative renal failure. As in other cardiac surgery, preoperative renal failure predicted increased operative mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…スクの高い手術法であり,その手術成績は良好とはいえな い.特に術前にショック状態を呈する場合や,術後に遺残 短絡を認める症例の予後は悪い [1][2][3][4][5] .Komeda, David らに より infarct exclusion 法が発表 6…”
Section: 心筋梗塞後の心室中隔穿孔に対する手術は,現在でもリunclassified